Review on Cholesterol Metabolism and Mechanism-Based Pharmacotherapy - Cheolin PARK (Asian Journal of Pharmaceutical Research and Development, 2026)
Cholesterol is an indispensable lipid molecule that contributes to membrane structure, cellular signaling, and the synthesis of steroid hormones and bile acids. Nevertheless, chronic elevation of circulating cholesterol, particularly low-density lipoprotein cholesterol (LDL-C), is a well-established causal factor in atherosclerotic cardiovascular disease (ASCVD). Continuous progress in molecular pharmacology has clarified the regulatory networks governing cholesterol homeostasis and has enabled the development of therapeutics precisely targeting these pathways. This review systematically summarizes the physiological mechanisms of cholesterol absorption, biosynthesis, transport, and elimination, and critically examines mechanism-based pharmacotherapies currently used or under development. Emphasis is placed on molecular targets, pharmacological mechanisms, and clinical relevance, with a focus suitable for pharmaceutical sciences. The integration of mechanistic insight with therapeutic strategy underscores the evolving role of precision pharmacotherapy in cholesterol management.